Evaluation of chromosomal damage, cytostasis, cytotoxicity, oxidative DNA damage and their association with body-mass index in obese subjects - Donmez-Altuntas, Hamiyet; Sahin, Fatma; Bayram, Fahri; Bitgen, Nazmiye; Mert, Meral; Guclu, Kenan; Hamurcu, Zuhal; Arıbas, Sülbiye; Gundogan, Kursat; Diri, Halit (Mutation research. Genetic toxicology and environmental mutagenesis, 2014)
•CBMN-cyt assay parameters and plasma 8-OHdG concentrations were evaluated in obese subjects.•Frequencies of MN, NPB and NBUD, apoptotic and necrotic cells in obese subjects were higher than in normal-weight subjects.•Plasma 8-OHdG concentrations in obese subjects were lower than in normal-weight subjects.•Frequencies of MN, NPB and NBUD are positively correlated with BMI in all subjects. Over-weight and obesity are serious problems that increase the risk not only for chronic diseases like diabetes and heart disease but also of various types of cancer. This study was conducted to evaluate cytokinesis-block micronucleus cytome (CBMN-cyt) assay parameters and plasma concentrations of 8-hydroxy-2′-deoxyguanosine (8-OHdG), and their relationship with age, body-mass index (BMI) and waist-to-hip ratio (WHR) in 83 obese, 21 over-weight and 21 normal-weight subjects. Frequencies of micronuclei (MN), nucleoplasmic bridges (NPB), nuclear buds (NBUD), and apoptotic and necrotic cells in lymphocytes of obese subjects were found to be significantly higher than those found in normal-weight and over-weight subjects (p<0.01 and p<0.05), whereas plasma concentrations of 8-OHdG in obese subjects were lower than those observed in normal-weight and over-weight subjects (p<0.05 and p<0.01, respectively). There was a negative correlation between age and frequency of necrotic cells and NDI (p<0.05), whereas there was no correlation between BMI, WHR, CBMN cyt assay parameters and plasma 8-OHdG in normal-weight subjects. In over-weight subjects, a negative correlation was observed between age and NDI (p<0.01) and a positive correlation between age and frequency of NPB (p<0.01) and between BMI and frequency of NBUD (p<0.05). In obese subjects, a negative correlation was observed between age and NDI (p<0.01) and between BMI and NDI (p<0.05), whereas no correlation was observed between WHR and CBMN-cyt assay parameters and plasma 8-OHdG. However, frequencies of MN, NPB, NBUD, apoptotic and necrotic cells in total over-weight/obese (p<0.01/p<0.05) and all subjects (p<0.01) increased with increasing BMI. The increase in genomic damage (MN, NPB and NBUD) in obese subjects and the positive correlation between genomic damage and BMI in total over-weight/obese subjects indicate that obesity increases genomic damage and may be associated with an increased risk of cancer, because an increase in MN frequency is a predictor of cancer risk.